Biological Aspects of Shortfin Scad (Decapterus macrosoma) in Makassar Waters, South Sulawesi, Indonesia. (April 2019) - Asni, A; Hamsiah,; Rustam,; Ilmiah,
Abstract: The shortfin scad is a pelagic fisheries resource that plays an important role in the economy of the South Sulawesi marine fisheries sector. Besides its use for consumption by local communities, shortfin scad are also used as bait in the tuna fishery and exported frozen. Over the past five years there has been a decline in catches caused by uncontrolled exploitation. To date, there is still no control over the exploitation of shortfin scad, and it is feared the sustainability of shortfin scad as a fisheries resource is threatened. This research aimed to analyse specific aspects of shortfin scad biology for this population, including sex ratio, size at first maturity, and growth pattern. The study was conducted in the waters off Makassar, in South Sulawesi, Indonesia, using direct observation with a survey method. Fish samples were obtained from catches landed by fishermen at the Paotere fishing harbour in Makassar City. Sampling was conducted from early April to early August 2017. The shortfin scad sample obtained comprised 201 male fishes and 169 female fishes. The results showed that the sex ratio of the shortfin scad (male:female) was 1.1:1.0. The shortfin scad reached first maturity at a fork length of 18.24 − 19.54 cm for males and 16.45 − 17.24 cm for females. The Gonad Maturity Index (GMI) of male fish was dominated by immature gonad classes (GMI I and GMI II), while for females GMI III and GMI IV dominated the sample, indicating that females mature earlier than males. Male and female growth patterns were allometric positive with b>3, indicating that the gain in weight was faster than the increase in length.